2013
DOI: 10.1002/sia.5248
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between parameter variation and oxide structure of a modified PAA process

Abstract: In the present work, the robustness of an anodizing process was tested. Important anodizing parameters such as the anodizing potential, the dwell time at the anodizing potential, and the bath temp. were varied. The influence of the parameter variation on the microstructure of the oxide layers was investigated by SEM. It could be shown that the pore diam. as well as the layer thickness reacts very sensitively on the alternating parameters. The barrier layer thickness clearly depends on the anodizing voltage but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 20 publications
6
23
0
Order By: Relevance
“…2. Under the concentration and potential conditions, as in SAA20 and SAA50, the oxide thickness increases with an increasing anodizing temperature, in accordance with Schneider et al 11 The thickness of the barrier layer generally corresponds to the applied voltage following the 1.2 nm/V relation. 4 The relation accurately predicts the barrierlayer thickness of both SAA oxides, while the measured values for PSA oxides are slightly larger than expected.…”
Section: Resultssupporting
confidence: 79%
“…2. Under the concentration and potential conditions, as in SAA20 and SAA50, the oxide thickness increases with an increasing anodizing temperature, in accordance with Schneider et al 11 The thickness of the barrier layer generally corresponds to the applied voltage following the 1.2 nm/V relation. 4 The relation accurately predicts the barrierlayer thickness of both SAA oxides, while the measured values for PSA oxides are slightly larger than expected.…”
Section: Resultssupporting
confidence: 79%
“…Anodizing methods for creating nanofeatured films in aluminum and titanium have been extensively studied under a variety of different conditions [59], [60], [61].…”
Section: B Background On Techniquementioning
confidence: 99%
“…From these studies, the observed results from differing voltage and dwell times have established that there is a direct correlation between voltage and barrier layer thicknesses [59]. These anodizing methods used a variety of different acidic electrolytes at varying concentrations to include sulfuric acid, oxalic acid and phosphoric acid [60].…”
Section: B Background On Techniquementioning
confidence: 99%
See 2 more Smart Citations